The experience and challenges of healthcare-reform-driven medical consortia and Regional Health Information Technologies in China: A longitudinal study. (November 2019) - Liang, Jun; Zheng, Xu; Chen, Zhenying; Dai, Siqi; Xu, Jie; Ye, Hui; Zhang, Zhongan; Ge, Fangmin; Lei, Jianbo
Highlights: The Chinese government used RHIT to support the development of medical consortia and achieved significant results. The Bass model can be used to predict the increment of Chinese hospitals joining medical consortia. The government's goal i.e. 90% of hospitals should join medical consortia will likely be realized by 2020. Abstract: Objective: To achieve universal access to medical resources—a partial goal of the second ambitious health reform since 2010—the Chinese government aimed to build a regional medical consortium and enhance the efficiency of health information exchange (HIE). We analyzed the experience of constructing a medical consortium in Chinese hospitals, which was based on regional health information technology (RHIT) promoted by HIE. Method: In this longitudinal study, we analyzed the results of the annual surveys that were conducted by the China Hospital Information Management Association from 2006 to 2015. The survey results mainly concerned whether hospitals should join the regional medical consortium, the methods used for sharing inter-hospital medical data, and the out-of-hospital information interaction system. The Bass diffusion model was adopted to fit and predict the proportion of Chinese hospitals joining the consortium from 2006 to 2025. Result: As of 2015, the survey results of 7272 hospitals were obtained. The proportion of hospitals in partnership systems increased from 3.0% in 2007 to 57.2% in 2015. There has been a rapid development in the electronic sharing of medical data between hospitals. The proportion of hospitals that relied solely on paper documents for data interaction decreased from 43.3% in 2011 to 8.0% in 2015. There was a strong positive linear correlation between hospitals joining the consortium and the accessibility of electronic medical data exchange within hospitals (r = 0.925). The proportions of hospitals that supported dual referral systems and appointments, data browsing between hospitals and regional information systems, and remote consultation services increased to 65.0%, 61.6%, and 81.9% in 2015, as compared to 18.8%, 16.8%, and 10.9% in 2011, respectively. The Bass prediction model showed that the goal of recruiting 90% of the hospitals to the consortium by 2020 will likely be achieved (adjusted R 2 = 0.93). Conclusion: The Chinese government has applied a top-down, high-level design model to promote the rapid development of a medical consortium, in which the RHIT technologies are crucial technical enabler.